2010
DOI: 10.1016/j.limno.2009.11.001
|View full text |Cite
|
Sign up to set email alerts
|

What drives the evolution of the sedimentary phosphorus cycle?

Abstract: a b s t r a c tThe 'Chicken Creek' artificial catchment area, Welzow-South, E Germany, created to study processes and structures of initial ecosystem development, discharges into a small experimental lake (A =3805 m 2 , V= 3992 m 3 , z max = 2.4 m). This lake was man-made in 2005 and filled by natural surface runoff until January 2006. In summer 2006 and 2008, the actual development of sediments and the evolution of the phosphorus (P) cycle were studied. 19.7% of the original lake volume was filled by sediment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…It is known that roots of studied species M. spicatum release oxygen that has profound affect on mineralization processes in the sediment (Laskov et al 2006). Kleeberg et al (2010) reported that macrophytes drive the evolution of a sedimentary P cycle by mobilizing and translocating P, by accumulating carbon, and thus by stimulating microbial and redox processes. The wellaerated sediment in Lake Bohinj enables rapid mineralization of organic matter and, in turn, sufficient nutrients for growth of macrophytes.…”
Section: Relationship Between Macrophytes and Sedimentsmentioning
confidence: 99%
“…It is known that roots of studied species M. spicatum release oxygen that has profound affect on mineralization processes in the sediment (Laskov et al 2006). Kleeberg et al (2010) reported that macrophytes drive the evolution of a sedimentary P cycle by mobilizing and translocating P, by accumulating carbon, and thus by stimulating microbial and redox processes. The wellaerated sediment in Lake Bohinj enables rapid mineralization of organic matter and, in turn, sufficient nutrients for growth of macrophytes.…”
Section: Relationship Between Macrophytes and Sedimentsmentioning
confidence: 99%
“…The decomposition of OM, especially via iron and sulphate reduction, is crucial for the mobilisation of inorganic P, bound by sorption to iron hydroxide surfaces (Kleeberg et al 2010). Due to aerobic and anaerobic redox processes, not only organic C compounds but also organic P compounds are turned over (Turner et al 2005;Kleeberg et al 2010).…”
Section: Mobile Phosphorusmentioning
confidence: 99%
“…Due to aerobic and anaerobic redox processes, not only organic C compounds but also organic P compounds are turned over (Turner et al 2005;Kleeberg et al 2010). The low C/N ratios (<9) indicate that the NaOH extractable organic P compound groups included in the precipitate originate from autochthonous matter (Punning et al 2008).…”
Section: Mobile Phosphorusmentioning
confidence: 99%
“…Sediment particles smaller than 100 lm were used for all analyses and acid digestion. The proportion of organic matter (OM) in the sediment can be reflected by weight loss through combustion (450°C, 3 h) (Kleeberg et al 2010). To determine the metal and nutrient contents, sediment samples were digested by H 2 SO 4 and H 2 O 2 (Kleeberg et al 2010).…”
Section: Methodsmentioning
confidence: 99%
“…The proportion of organic matter (OM) in the sediment can be reflected by weight loss through combustion (450°C, 3 h) (Kleeberg et al 2010). To determine the metal and nutrient contents, sediment samples were digested by H 2 SO 4 and H 2 O 2 (Kleeberg et al 2010). Major elements such as P and metals were determined by Inductively Coupled Plasma Optical Emission Spectrometer (ICP-OES, Optima 5300DV).…”
Section: Methodsmentioning
confidence: 99%